I've tried being nice : essays - Leary, Ann (Marysue Rucci Books, 2024)
"Having arrived at a certain age (her prime), Ann Leary casts a wry backward glance at a life spent trying -- and often failing -- to be nice. With wit and surprising candor, Leary recounts the bedlam of home bat invasions, an obsession with online personality tests, and the mortification of taking ballroom dance lessons with her actor husband. She describes hilarious red-carpet fiascos and other observations from the sidelines of fame, while also touching upon her more poignant struggles with alcoholism, her love for her family, her dogs, and so much more. Prepare to laugh, cry, cringe and revel in the comically relatable chaos of Ann Leary's life as revealed in this delightful collection of essays."--